2007
DOI: 10.1038/sj.bjc.6603714
|View full text |Cite
|
Sign up to set email alerts
|

Borderline breast core needle histology: predictive values for malignancy in lesions of uncertain malignant potential (B3)

Abstract: Breast core needle biopsy (CNB) is an accurate test but may result in borderline histology (lesions of uncertain malignant potential or B3). This is an evaluation of the largest series (to date) of B3 histology, which focusses on estimating positive predictive values (PPV) for malignancy. We identified all B3 CNBs over a 10-year period in a single institution (N ¼ 372) from a series of 4035 consecutive needle biopsies. We describe the imaging findings, and report excision histology outcomes (N ¼ 279) and categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
83
11
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 21 publications
17
83
11
10
Order By: Relevance
“…A total of 14% (n=300) of the lesions were B3-lesions (lesions of uncertain malignant potential) and 95 patients were (14) 3 (3) PPV, positive predictive value; LIN, lobular intraepithelial neoplasia; ADH, atypical ductal hyperplasia; PL, papillary lesion; FEA, flat epithelial atypia; RS, radial scar; PT, phyllodes tumor. (4,(9)(10)(11)(12). In our trial, ADH was the biggest subgroup of the B3-lesions, with 31%; similar observations have been made by other authors (5).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A total of 14% (n=300) of the lesions were B3-lesions (lesions of uncertain malignant potential) and 95 patients were (14) 3 (3) PPV, positive predictive value; LIN, lobular intraepithelial neoplasia; ADH, atypical ductal hyperplasia; PL, papillary lesion; FEA, flat epithelial atypia; RS, radial scar; PT, phyllodes tumor. (4,(9)(10)(11)(12). In our trial, ADH was the biggest subgroup of the B3-lesions, with 31%; similar observations have been made by other authors (5).…”
Section: Discussionsupporting
confidence: 76%
“…The overall risk for malignancy of B3-lesions was 22% in our study; in 23 cases, postsurgical histological examination revealed a malignancy. Other studies reported an incidence of 8-35% (4)(5)(6)13,(18)(19)(20). The highest malignancy rate regarding the subgroup of the B3-lesions was found for ADH, with a PPV of 0.31.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to mention that calcification was frequently associated with epithelial atypia, particularly ADH, and LCIS and it was rare in papillary lesions, radial scars and cellular fibroepithelial lesions. Our results support the findings of previous studies, 7,12,17,18 and emphasize that the clinical and radiological features are helpful in deciding further management after a B3 needle core biopsy diagnosis, that this should form part of the evidence discussed at multidisciplinary meetings and the management decision should be tailored to individual patient circumstances.…”
supporting
confidence: 80%
“…The B3 category consists of a heterogeneous group of lesions which may yield only benign histology on initial NCB sampling but are recognized to show heterogeneity and may harbor malignancy elsewhere or to have an increased risk of associated adjacent malignancy. 5,6 Although the B3 category constitutes a relatively small proportion of all NCB (3-9%; average 6% 4,[7][8][9][10][11][12] ), most cases progress to surgical intervention to establish an excision histology diagnosis. This has significant implications particularly in screen-detected (nonsymptomatic) breast lesions in which final benign diagnoses after surgical intervention is a drawback of mammographic screening.…”
mentioning
confidence: 99%
“…MRI-guided vacuumassisted breast biopsy (MRgVABB) is a safe and accurate technique for evaluation of otherwise occult MRI-detected breast lesions [6][7][8][9][10][11][12]. However, a considerable proportion of lesions diagnosed on percutaneous breast biopsies are classified as high-risk lesions [13]. The high-risk histology includes atypical ductal hyperplasia (ADH), lobular neoplasia (LN) (regrouping of the former atypical lobular hyperplasia (ALH) and lobular carcinoma in situ (LCIS)), flat epithelial atypia (FEA), papillary lesions, radial scar/complex sclerosing lesion, phyllodes tumour, and mucocele-like lesions [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%